2016
DOI: 10.1007/s00586-016-4746-3
|View full text |Cite
|
Sign up to set email alerts
|

Laminoplasty versus laminectomy with fusion for the treatment of spondylotic cervical myelopathy: short-term follow-up

Abstract: This study provides evidence that laminoplasty may be superior to laminectomy with fusion in preserving cervical range of motion, reducing hospital stay and minimizing cost. However, the significance of these differences remains unclear, as laminoplasty clinical outcome scores were generally comparable to laminectomy with fusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
61
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 37 publications
12
61
0
2
Order By: Relevance
“…Patients after ACCDF (16.8%, 95% CI 6.9%–27.2%) and ACDF (16.2%, 95% CI 11.7%–19.8%) had higher incidence than those who received ACCF (9.9%, 95% CI 4.8%–15.9%). Multifactors as reported by recent studies, [63,6871,7580] hematoma, pharyngeal plexus denervation, vocal cord paralysis, adhesion formation, plate profile, and swelling due to biologic agents, may be related to dysphagia. Brad [99] indicated that a no-profile cervical disc arthroplasty had a significantly lower rate of dysphagia compared with ACDF.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Patients after ACCDF (16.8%, 95% CI 6.9%–27.2%) and ACDF (16.2%, 95% CI 11.7%–19.8%) had higher incidence than those who received ACCF (9.9%, 95% CI 4.8%–15.9%). Multifactors as reported by recent studies, [63,6871,7580] hematoma, pharyngeal plexus denervation, vocal cord paralysis, adhesion formation, plate profile, and swelling due to biologic agents, may be related to dysphagia. Brad [99] indicated that a no-profile cervical disc arthroplasty had a significantly lower rate of dysphagia compared with ACDF.…”
Section: Discussionmentioning
confidence: 82%
“…Twenty-five studies [20,2325,33,35,36,40,47,51,59,61,62,68,69,7376,78,85,86,91,117,118] containing 142 patients with infection of 3489 patients after cervical surgery were included. Figure 21 shows that the incidence was 2.8% (95% CI 1.7%–4.0%), with substantial heterogeneity of incidence observed.…”
Section: Resultsmentioning
confidence: 99%
“…Several reports have described reductions in ROM of 30% to 70% of the preoperative ROM after cervical laminoplasty 6,20) . Blizzard et al reported that the ROM was reduced by up to 27.11% of the preoperative ROM after cervical LF 2) . In our study, patients in the cervical LF group experienced a significant reduction in ROM compared with those in the EL group.…”
Section: Rommentioning
confidence: 96%
“…Posterior decompression surgeries such as cervical expansive laminoplasty (EL) or laminectomy with fusion (LF) have been widely performed to adequately decompress the spinal cord, although they cannot directly remove ossification of the posterior longitudinal ligament (OPLL) 2,7,11) . In patients with cervical myelopathy with OPLL in more than three segments, posterior decompression is more attractive than anterior decompression because this procedure can avoid the need for an anterior route or major strut graft-related problems, such as cerebrospinal fluid leakage, pseudoarthrosis, or graft dislodgment 26,31) .…”
Section: Introductionmentioning
confidence: 99%
“…Eine Überlegenheit eines Verfahrens hinsichtlich der Verbesserung der klinischen Symptomatik und der postoperativen Stellung der Halswirbelsäule, hier insbesondere der Ausbildung einer Kyphose, findet sich nicht. Allerdings gibt es Hinweise dass die Komplikationsquote bei Laminektomie plus Fusion höher ist als bei der Laminoplastie [19]. Ein neues posteriores Verfahren ist die unilaterale Laminotomie/Hemilaminektomie mit bilateraler Dekompression in Undercutting-Technik [20]; hier stehen allerdings noch belastbare klinische und radiologische Daten aus.…”
Section: Operative Therapie Bei Zervikaler Spondylose: Posteriore Verunclassified